1990
DOI: 10.1007/bf00195890
|View full text |Cite
|
Sign up to set email alerts
|

The presence of glycollate oxidase and dehydrogenase in Dunaliella primolecta

Abstract: Homogenates of Dunaliella primolecta, D. salina and D. tertiolecta were assayed for glycollate oxidase and glycollate dehydrogenase. Both D. primolecta and D. salina but not D. tertiolecta showed substantial glycollate-dependent O2-uptake which is characteristic of glycollate oxidase. L-Lactate was an alternative substrate and both glycollate- and L-lactate-dependent O2 uptake were insensitive to 2 mM cyanide. Glycollate dehydrogenase, measured by following the glycollate-dependent reduction of 2,6-dichlorophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Also, hydroxypyruvate reductase was identified only in the mitochondria and not in the peroxisomes. According to our data the peroxisomes of D. primolecta are altogether not of the leaf-type as suggested by the results of Nimer et al (1990), but of the Eremosphaeratype which is characteristic of chlorophycean algae (Stabenau , 1992(Stabenau , 1992a. In accordance with this fact the distribution pattern of hydroxyacyl-CoA dehydrogenase (Fig.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…Also, hydroxypyruvate reductase was identified only in the mitochondria and not in the peroxisomes. According to our data the peroxisomes of D. primolecta are altogether not of the leaf-type as suggested by the results of Nimer et al (1990), but of the Eremosphaeratype which is characteristic of chlorophycean algae (Stabenau , 1992(Stabenau , 1992a. In accordance with this fact the distribution pattern of hydroxyacyl-CoA dehydrogenase (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…Therefore, previously published data indicating the presence of glycolate oxi- 0-0~0 I~ 9 .i"I" \ for only 45 min, therefore the peroxisomes did not reach their specific density. Enzyme activities: 10 units correspond to the following activities per ml fraction: cytochrome C oxidase, 200 pkat; malate dehydrogenase, 250 nkat; glycolate dehydrogenase, 20 pkat; hydroxypyruvate reductase, 600 pkat; hydroxyacyl-CoA dehydrogenase, 300 pkat; uricase, 100 pkat dase in D. salina (Nimer et al 1990) could not be confirmed. As with D. primolecta, glycolate dehydrogenase along with hydroxypyruvate reductase is located exclusively in the mitochondria, while the peroxisomes appear to be of the Eremosphaera-type.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This means that such isozymes, if present in Cyanophora, would produce normal and identical Michaelis-Menten kinetics with glycolate as a varied substrate but different kinetics with oxygen as varied substrate. To date, however, there have been only two reports that two glycolate-oxidizing enzymes, GO and GD, would occur together in the same organism (25,26). Thus, it is more probable that Cyanophora has only one enzyme that can bind oxygen cooperatively.…”
Section: Identification Of Gomentioning
confidence: 99%
“…The observed increasing cellular ROS levels during oil exposure under increasing inhibition of photorespiration confirms anti-oxidation as one of the physiological functions. In addition, several studies have shown that the glycolate secreted by Dunaliella tertiolecta and other species of Dunaliella is then reassimilated in ROLE OF CORE METABOLISM DURING OIL EXPOSURE the cells (Nimer et al 1990, Sciandra et al 1997, Leboulanger et al 1998, through the action of glycolate oxidase or glycolate dehydrogenase into the glyoxlate pathway (Nimer et al 1990, Stabenau et al 1993. Moroney et al (2013) suggested photorespiration "limits" the loss of carbon by oxygenation by RuBisCO, as only one molecule of CO 2 is lost after accounting for glycolate oxidase or glycolate dehydrogenase activity.…”
Section: Discussionmentioning
confidence: 99%